PENURUNAN BOD PADA BIOGAS KOTORAN SAPI CAMPURAN LIMBAH CAIR INDUSTRI PENYAMAKAN KULIT DENGAN VARIASI KECEPATAN DAN LAMA PENGADUKAN - Indrawati, Rosiana (Journal of Research and Technology, 2017)
The scarcity of energy sources, especially fuel oil (BBM) has become a world problem. The abundant cattle dung in the community has not been optimally utilized. In addition, the Tannery Industry (IPK) has not been optimally utilized. The aim of this research was to know the effect of speed and stirring duration to biogas volume and final BOD concentration on cow manure biogas mixed with tannery industry wastewater (IPK). The experiment used biodigester reactor as much as five pieces, one unit as a controller without stirring and four other unit as the test digester with stirring. IPK 0 as a control digester without stirring. Variation of stirring speed were 5 and 10 rpm, and stirring time were 10 and 15 minutes. The volume of biogas was measured for 20 days. BOD level was measured on the last day of fermentation process. The experiment results showed that the highest biogas volume was found on PK10L10 test digester that was mixture of cow manure and tannery industry wastewater (IPK) with variation of 10 rpm and duration of stirring 10 minutes ie 0.904 m3, and the lowest biogas volume was 0,158 m3 in IPK0 digester. The highest decreasing in BOD content was 20% in PK10L15 digester and the lowest decreasing IPK0 digester was 4%. The stirring process had a significant effect on biogas production and decreased BOD concentration in the digester. Keywords: BOD, Tannery Industry Wastewater, Biogas, Cow Manure.